Evaluating the effects of Contract Farming Practice on Production Output in Cotton Industry. Case of Cottco (pvt) ltd Company. - Tumai, Kelvin (Midlands State University, 2017)
The researcher focused on the effects of contract farming practice on production output in cotton industry. The cotton companies of Zimbabwe has experience a decline in production output. The study also gives the challenges faced by the companies in cotton sector and this was done by focusing on the Cotton Company of Zimbabwe (Cottco). The researcher attempt to answer objectives like the effects of contract farming on production output on production output as well as challenges affects cotton production output. The literatures were reviewed to give the interpretations evaluating of various theories and schools of thoughts regarding contract farming practice. Due to the quantitative of the study, an explanatory survey was used as research methodology with questionnaires and interviews being the major research instruments and a sample size of sixty elements was used. The participants included the departments’ staff of Cottco (pvt) ltd and farmers in contract farming. Both probability and non probability sampling techniques was used in selecting a sample. The data collected was analysed and presented in form of tables and graphs to make substantial interference. The findings from the research were that there is significant positive relationship between contract farming practice and production output. The recommendations such as horizontal integration, large scale contract farming, and seeking government support, competitive based pricing strategy and legal action against side marketing was made. Conclusions on the findings were drawn as per the objectives met. Suggestions for further studies were made to allow future research of the case under study as well as to other cotton companies.